Obstetric anesthesia - Palmer, Craig M.; D'Angelo, Robert; Paech, Michael J. (New York ; Oxford : Oxford University Press, 2011)
'Obstetric Anaesthesia' is an ideal introduction to the specialty as well as an essential daily guide for obstetric patient care and management.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anesthesia in obstetrics